2020
DOI: 10.1007/s10494-020-00197-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of Bivariate 2D-EMD for the Analysis of Instantaneous Flow Structures and Cycle-to-Cycle Variations of In-cylinder Flow

Abstract: EMD for the analysis of instantaneous flow structures and cycle-to-cycle variations of in-cylinder flow', Flow, Turbulence and Combustion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…It was applied to a velocity field constructed with a large-scale organised synthetic vortex and relatively small-scale isotropic homogeneous turbulence. Subsequently, the methodology was also applied to high-speed PIV measurements in the symmetry plane of the tumble of an optically accessible engine [10]. Both results confirmed that the turbulent part could be separated from the large-scale organized motion based only on the instantaneous velocity field, following:…”
Section: Flow Analysis Tools 41 2d Multivariate Empirical Mode Decomp...mentioning
confidence: 58%
See 4 more Smart Citations
“…It was applied to a velocity field constructed with a large-scale organised synthetic vortex and relatively small-scale isotropic homogeneous turbulence. Subsequently, the methodology was also applied to high-speed PIV measurements in the symmetry plane of the tumble of an optically accessible engine [10]. Both results confirmed that the turbulent part could be separated from the large-scale organized motion based only on the instantaneous velocity field, following:…”
Section: Flow Analysis Tools 41 2d Multivariate Empirical Mode Decomp...mentioning
confidence: 58%
“…R2P1. As confirmed in [10], EMD is suitable for the analysis multi-cycle flow fields in engines as it is not limited by a statistical convergence criterion. Other decomposition methodologies exist in the literature.…”
Section: Flow Analysis Tools 41 2d Multivariate Empirical Mode Decomp...mentioning
confidence: 94%
See 3 more Smart Citations